Kesenjangan Bahan Ajar Dengan Tahap Operasi Formal - Sri Wahyuni (Pedir Research Institute, 2021)
Teaching materials are one of the important essences in the implementation of education, especially formal education. The material presented in the teaching materials is adjusted or guided by the education curriculum based on the Regulation of the Minister of Education and Culture Number 20 Year 2016. One of the important considerations in the regulation is the competency of graduates of educational units with the dimension of knowledge. The dimensions of student knowledge are of course adapted to the aspect of individual cognitive development in the psychological sphere, one of which leads to the realm of formal operating reasoning at the junior high school level.